A Case Study of Health Expenditure in India - Kalpanapriya, D.; Mubashir Unnissa, M.; Sekar, Rakshanya (International Journal of Engineering and Technology, 2018)
The article aims in analysing healthcare expenditure of India, as it struggles to meet the health care requirements of all the citizens. In order to acheieve this, it is important to understand the trends in healthcare expenditure of the country to create a sustainable health expenditue model. Post millenium, with various reforms and increased awareness, a certain redistribution can be observed among different arms that contribute to total healthcare expenditure.This study reviews and summarise the expenditure trends between the years 2004 and 2014. Numerical illustrtions are also provided to show the government and private sectors contributions on the health care products.Â